Mycobacterium tuberculosis low molecular weight T‐cell antigen Mtb8.4 has heme‐binding and fiber‐forming properties. Issue 20 (18th July 2022) - Singh, Rashika; Kundu, Prasun; Bhattacharje, Gourab; Das, Amit Kumar
Abstract : Mtb8.4, a secretory T‐cell antigen of Mycobacterium tuberculosis, is important for providing an antigen‐specific immune response. In this study, we showed Mtb8.4 to have both heme‐binding and fibril‐forming properties, using experimental and in silico methods. High absorbance at 410 nm and interaction with hemin‐agarose demonstrated its heme‐binding nature. Titration of Mtb8.4 with heme resulted in 1 : 1 stoichiometry. The heme‐binding pocket in Mtb8.4 was identified by molecular modeling, and binding residues were predicted using molecular docking. The molecular dynamics simulations of apo‐ and heme‐bound Mtb8.4 confirmed that the heme group forms a stable complex. Transmission electron microscopy analyses and dye‐binding assays showed that Mtb8.4 forms fibers. Computational studies predicted that the C‐terminal sequence ( 93 AAQYIGLVESV 103 ) is important for forming fibers. In silico analyses further anticipated the probable epitope ( 82 AMAAQLQAV 90 ) of Mtb8.4. The fiber‐forming properties of Mtb8.4 could be advantageous from a vaccine perspective for aggregate/fibril‐based vaccine delivery or it might influence the epitope presentation of Mtb8.4. Abstract : The paper characterized a novel secretory protein, Mtb8.4, a low molecular weight T‐cell antigen from Mycobacterium tuberculosis . Here, we have experimentally demonstrated that Mtb8.4 is a heme‐binding and fiber‐forming protein. Probable heme‐binding residues have been predicted in silico . Molecular dynamics simulations further showed that Mtb8.4 binds heme stably in solution. The protein region responsible for fiber formation has been explored.